2021
DOI: 10.1038/s41598-021-00229-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage response of haematopoietic stem and progenitor cells to high-LET neutron irradiation

Abstract: The radiosensitivity of haematopoietic stem and progenitor cells (HSPCs) to neutron radiation remains largely underexplored, notwithstanding their potential role as target cells for radiation-induced leukemogenesis. New insights are required for radiation protection purposes, particularly for aviation, space missions, nuclear accidents and even particle therapy. In this study, HSPCs (CD34+CD38+ cells) were isolated from umbilical cord blood and irradiated with 60Co γ-rays (photons) and high energy p(66)/Be(40)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Flow cytometry analysis of Annexin V- and 7-amino-actinomycin-positive cells exposed to different doses of γ-rays or boron ions reveals a three-fold increase in apoptosis 48 h after exposure to high-LET ions as compared to low-LET IR [ 50 ]. Another report came to similar conclusions [ 65 ] and demonstrated increased levels of late apoptosis in hematopoietic and progenitor cells exposed to low doses of neutrons. Neutron irradiation also increases the rates of early apoptosis in osteosarcoma cells, as compared to γ-rays and is associated with enhanced Caspase-3 and Caspase-9 expression and cleavage, PARP-1 cleavage and increased reactive oxygen species production [ 66 ].…”
Section: Exposure To High-let Ir Activates Signaling Network Mainly R...supporting
confidence: 63%
“…Flow cytometry analysis of Annexin V- and 7-amino-actinomycin-positive cells exposed to different doses of γ-rays or boron ions reveals a three-fold increase in apoptosis 48 h after exposure to high-LET ions as compared to low-LET IR [ 50 ]. Another report came to similar conclusions [ 65 ] and demonstrated increased levels of late apoptosis in hematopoietic and progenitor cells exposed to low doses of neutrons. Neutron irradiation also increases the rates of early apoptosis in osteosarcoma cells, as compared to γ-rays and is associated with enhanced Caspase-3 and Caspase-9 expression and cleavage, PARP-1 cleavage and increased reactive oxygen species production [ 66 ].…”
Section: Exposure To High-let Ir Activates Signaling Network Mainly R...supporting
confidence: 63%
“…Then, HSPCs were purified by using CD34 + immunomagnetic beads (human CD34 + Microbead kit, Miltenyi Biotec Inc., Bergisch Gladbach, Germany) according to the manufacturer’s guidelines. CD34+ purity and viability were checked as previously described by Engelbrecht et al 35 . Flow cytometric analysis revealed an average CD34 + purity of 95.47% (SD: 3.62%) and a viability minimum was set at 95%.…”
Section: Methodsmentioning
confidence: 99%
“…After irradiation, cells of one vial were seeded out in two wells of a 48-well suspension plate (Greiner Cellstar ® , Sigma-Aldrich). The cells were stimulated into division and the CD34 + micro-culture CBMN assay was performed as recently described by Engelbrecht et al 35 . The nuclear division index (NDI) provides a measure of the cell’s proliferative status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic instability results in a high frequency of mutation, including chromosomal rearrangements, aneuploidy and changes in nucleic acid sequences [5]. An increase in DNA damage caused by processes such as irradiation or a decrease in DNA repair activity promotes genomic instability [6]. Many studies have also indicated that various therapeutic methods, such as radiotherapy, chemotherapy, and targeted therapy, induce genomic instability, subsequently increasing tumor heterogeneity and ultimately leading to recurrence [7].…”
Section: Introductionmentioning
confidence: 99%